PENGARUH FAKTOR INTERNAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA SUBSEKTOR ANEKA INDUSTRI TAHUN 2019-2022 - Ni Made Mahardini; Ni Putu Lisa Ernawatiningsih; I Ketut Sunarwijaya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
This study attempts to provide a deeper understanding of the relationship between internal company factors and firm value. The objective of this study is to examine the effects of dividend policy, business size, profitability, liquidity, and leverage on the value of firms across different industrial sub-sectors that are listed on the Indonesia Stock Exchange (BEI) between 2019 and 2022. Multiple linear regression is the data analysis technique employed, and the purposive sampling approach is utilized to pick the sample. Ten businesses that were watched for four years made up the research sample. The findings of the study indicate that while dividend policy, business size, and liquidity do not significantly affect a firm's value, leverage and profitability do have a favorable impact.